2007
DOI: 10.1016/j.molimm.2006.11.019
|View full text |Cite
|
Sign up to set email alerts
|

17β-Estradiol downregulates Kupffer cell TLR4-dependent p38 MAPK pathway and normalizes inflammatory cytokine production following trauma-hemorrhage

Abstract: Although studies have shown that 17β-estradiol (estradiol) normalized Kupffer cell function following trauma-hemorrhage, the mechanism by which E2 maintains immune function remains unclear. Activation of Toll-like receptor 4 (TLR4) initiates an inflammatory cascade, involving activation of p38 mitogen-activated protein kinase (MAPK), phosphatidylinositol 3-kinase (PI3K), and nuclear factor-κB (NF-κB). This leads to the release of proinflammatory cytokines. Thus, we hypothesized that the salutary effects of est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 50 publications
0
40
0
Order By: Relevance
“…Furthermore, the decreased Kupffer cell ATP and mtCOI levels were not observed in TLR4 mutant mice following trauma-hemorrhage, suggesting that downregulation of TLR4-dependent ATP production is critical to E2-mediated immunoprotection in Kupffer cells following trauma-hemorrhage (108). Activation of TLR4 initiates an inflammatory cascade involving activation of p38 MAPK, phosphatidylinositol 3-kinase (PI3K), and NF-κB, leading to the release of proinflammatory cytokines (109)(110)(111). Administration of E2 following traumahemorrhage in wild-type mice decreased Kupffer cell TLR4 expression, as well as prevented the phosphorylation of p38 MAPK and NF-κB, suggesting that the protective effect of estradiol on Kupffer cell function is mediated via downregulation of TLR4-dependent p38 MAPK and NF-κB signaling following traumahemorrhage-which prevents the systemic release of cytokines (109,110).…”
Section: Kupffer Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the decreased Kupffer cell ATP and mtCOI levels were not observed in TLR4 mutant mice following trauma-hemorrhage, suggesting that downregulation of TLR4-dependent ATP production is critical to E2-mediated immunoprotection in Kupffer cells following trauma-hemorrhage (108). Activation of TLR4 initiates an inflammatory cascade involving activation of p38 MAPK, phosphatidylinositol 3-kinase (PI3K), and NF-κB, leading to the release of proinflammatory cytokines (109)(110)(111). Administration of E2 following traumahemorrhage in wild-type mice decreased Kupffer cell TLR4 expression, as well as prevented the phosphorylation of p38 MAPK and NF-κB, suggesting that the protective effect of estradiol on Kupffer cell function is mediated via downregulation of TLR4-dependent p38 MAPK and NF-κB signaling following traumahemorrhage-which prevents the systemic release of cytokines (109,110).…”
Section: Kupffer Cellsmentioning
confidence: 99%
“…Activation of TLR4 initiates an inflammatory cascade involving activation of p38 MAPK, phosphatidylinositol 3-kinase (PI3K), and NF-κB, leading to the release of proinflammatory cytokines (109)(110)(111). Administration of E2 following traumahemorrhage in wild-type mice decreased Kupffer cell TLR4 expression, as well as prevented the phosphorylation of p38 MAPK and NF-κB, suggesting that the protective effect of estradiol on Kupffer cell function is mediated via downregulation of TLR4-dependent p38 MAPK and NF-κB signaling following traumahemorrhage-which prevents the systemic release of cytokines (109,110). Upon activation of TLR, MyD88, an adaptor protein that is shared by all TLR pathways, is recruited to TLR receptor domains and links TLR with the downstream intracellular signaling cascades (112,113).…”
Section: Kupffer Cellsmentioning
confidence: 99%
“…Such molecules, including fibronectin (80), heat shock proteins (81), and high-mobility group box 1 protein (82), may activate TLR4 to cause to the activation of the host immune system and the release of proinflammatory cytokines. Such activation of TLR4 in response to endogenous molecules during stress may explain the observation that the severity of various noninfectious models of critical illness are dependent on the activation of TLR4, including hemorrhagic shock (83)(84)(85)(86) and ischemia reperfusion injury (87)(88). The relative contribution of endogenous vs exogenous molecules in the activation of TLR4 in the pathogenesis of NEC remains of great scientific interest with respect to unraveling the complex origins of NEC.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown the involvement of Toll-like receptors (TLR) 4 and mitogen activated protein kinases (MAPK) in inflammatory response of cells such as Kupffer cells (Thobe, et al 2006; Frink et al 2007; Hsieh et al 2007). However, whether TLR4 and/or MAPK play(s) a role in keratinocytes following trauma-hemorrhage remains to be determined.…”
Section: Introductionmentioning
confidence: 99%